PENGEMBANGAN MEDIA PEMBELAJARANSCRAPBOOK PADA MATERI TUMBUHAN, SUMBER KEHIDUPAN DIBUMI KELAS IV SDN KEPANJEN 1 JOMBANG - Khasanah, Dian Nur; Raharja, Hawwin Fitra; Dwinata, Anggara (IJPSE Indonesian Journal of Primary Science Education, 2024)
This type of research uses research and development methods with ADDIE media, namely Analysis, Design, Development, Implementation, Evaluation. This model is used to solve problems in studying plant material and the sources of life on Earth. The subjects of this research were fourth grade students at SDN Kepanjen 1 Jombang. Data analysis used was field notes, validator questionnaires and student response questionnaires. This media was declared valid and appropriate by media expert validators with a percentage of 81% and material expert validators with an average of 87%. Apart from that, students' responses to the quality of scrapbook learning materials and media obtained an average score of 84%. The implementation was tested twice, namely on a small and large scale with results of 83%. Thus, it can be concluded that this scrapbook media can be applied to plant material and sources of life on earth and is well received.